The Role of Microteaching Course in Enhanching Pre-Service Teachers’ Self-Confidence During the Teaching Practice - Istiqomah, Annisa Nur; Karim, Sayit Abdul; Radjaban, R.Yohanes; Matas, Gordan (JOLLT Journal of Languages and Language Teaching, 2025)
Microteaching courses are crucial for equipping pre-service teachers with foundational skills through simulated teaching experiences before they enter actual classrooms. This mixed-methods study investigated how English Language Education Study Program (ELESP) pre-service teachers perceive the influence of microteaching courses on their self-confidence during PLP II teaching practice, and identified contributing factors. The study involved 27 ELESP pre-service teachers (9 male, 18 female) from Universitas Teknologi Yogyakarta, all of whom had completed microteaching courses and PLP II teaching practice. For the qualitative phase, six students were purposively selected for semi-structured interviews based on their high, middle, and low questionnaire scores, ensuring diverse perspectives on self-confidence during PLP II. Quantitative data was collected using a 4-point Likert Scale Scoring Rubric and analyzed, while qualitative interview data was analyzed using the interactive model adapted from Miles & Huberman (1994). Questionnaire results indicated that pre-service teachers’ self-confidence related to microteaching courses in PLP II teaching practice was in a "Good" category, with an average score of 78. Interviews revealed that self-concept was the most dominant influencing factor. This was shaped by internal aspects like material preparation and external elements such as peer and mentor-teacher feedback. Additionally, self-esteem was significantly impacted by external factors including student enthusiasm, attention, and mentor appreciation. This study distinguishes itself by focusing specifically on the role of microteaching in fostering pre-service teachers’ self-confidence. The implication is study may enhance pre-service teachers’ teaching skills and self-cconfidence, and serves as a reflection for the teacher educators to highlight the crucial role of microteaching in preparing pre-service teachers for school-based practice.